2007
DOI: 10.1021/ic070220e
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Hydrothermal Growth and Up-Conversion Emission of NaLnF4 (Ln = Y, Dy−Yb)

Abstract: The controlled hydrothermal preparation of NaYF(4) as both cubic and hexagonal phase types with specific associated morphologies, nanospheres and microtubes, respectively, has been achieved in the absence of organic solvents. The hexagonal NaYF(4) compound can be prepared in novel microtubular form and directly co-doped with Yb(3+)/Er(3+) ions. When excited by infrared light of 980 nm, these hexagonal NaYF(4) microtubes display strong green up-conversion emission, which was much more intense than that of cubic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(110 citation statements)
references
References 61 publications
2
106
1
1
Order By: Relevance
“…($200-450 C) owing to the dehydroxylation of RE(OH) 1 should also contain a small amount of REOF, as perceived from the existence of a right-hand tail in the amplied diffraction peak in Fig. 7b.…”
Section: 46mentioning
confidence: 99%
See 1 more Smart Citation
“…($200-450 C) owing to the dehydroxylation of RE(OH) 1 should also contain a small amount of REOF, as perceived from the existence of a right-hand tail in the amplied diffraction peak in Fig. 7b.…”
Section: 46mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] Among the investigated uorides, the Y(OH) 3Àx F x hydroxyuoride and YO (3Àx)/2 F x oxyuoride have been drawing great attention due to their significantly broader anion miscibility than their chloride and bromide counterparts of xed anion substitution phases. 16 It was also reported that Y(OH) 3Àx F x would decompose to YO (3Àx)/2 F x and a mixture of Y 2 O 3 and YOF when x $ 1 and x < 1, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Odlikuju se izvanrednom fotostabilnošću i niskom citotoksičnošću gde se pored izrade bioloških markera koriste i kao izvori svetlosti (fluorescentne lampe), u proizvodnji displeja (katodne cevi, plazma ekrani) i u zaštiti novčanica i dokumenata [1,2]. Fluoridi na bazi elemenata retkih zemalja tipa YF3 i NaYF4 predstavljaju idealnu matricu za ugradnju optički aktivnih jona retkih zemalja, jer poseduju visok stepen indeksa refrakcije, dobru hemijsku stabilnost i malu energiju fonona ~350-400 cm -1 [3,4].…”
Section: Uvodunclassified
“…Among them, the ternary metal fl uoride NaYF 4 has been demonstrated to be the most effective host matrix for up-conversion (UC) and down-conversion (DC) phosphors due to its low vibrational energy and high refractive index [31]. To achieve these phosphors, it is necessary to substitute Y 3+ by other rare earth ions having appropriate numbers of 4f electrons to facilitate f f transitions upon excitation [32,33]. Fortunately, this can be readily fulfilled as the Y 3+ ion in the crystal lattice of -NaYF 4 can be replaced by other rare earth ions in nearly any ratio [15].…”
Section: Characterization Of Typical -Nayf 4 Nanostructuresmentioning
confidence: 99%
“…Most of the UC nanoparticles were synthesized in organic solvents at high temperature [24,36,37] or in aqueous solutions [29,38,39] in the presence of organic additives. In the latter case, ethylenediaminetetraacetic acid (EDTA) [29,40] and trisodium citrate [38,41] have mainly been used as chelating ligands and their different chelating properties resulted in various morphologies [29,32,38,40]. In the present work, we report the synthesis of octahedral -NaYF 4 and its rare earth doped submicrometer particles in acetic acid.…”
Section: Characterization Of Typical -Nayf 4 Nanostructuresmentioning
confidence: 99%